Hedonic eating sensoriality in young people for the development of a healthy snack: Estudio de sensorialidad hedónica en jóvenes sobre snacks etiquetados como saludables - Flores Durán, Pablo; Abarza Álvarez, Daniel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
In the daily food diet, the collation or snack emerges as an essential food in young schoolchildren, who have direct access to its acquisition with a mainly unhealthy offer. Its presentation format, widely studied by the industry, serves as the basis for research carried out on young people between 14 and 18 years old (basic and secondary education students) from the southern zone of Chile, Temuco, on the hedonic quality characteristics that make decide the low but desired purchase of healthy snacks. The data obtained provide reasoned guidelines to promote the relevant development or design of this edible product.